Impact of Corporate Social Responsibility (CSR) on Brand Image and Consumer Preferences: A Case Study in the Automotive Industry - Nurul Septya Magisa; Ana Yuliana; Sulasti; Iswanto; Rizaldy (Universitas Muhammadiyah Palu, 2025)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) on brand image and consumer preference in the automotive industry, with a case study of motor vehicle consumers in Pontianak City. CSR is currently not only seen as a company's moral obligation, but also as a business strategy that can shape positive perceptions and create competitive advantages. This research uses a quantitative approach with a total of 100 respondents selected through purposive sampling technique. The research instrument was arranged in the form of a Likert scale closed questionnaire and analyzed by multiple linear regression. The results show that CSR has a significant effect on brand image and consumer preference, both directly and through brand image as an intervening variable. Brand image plays a strong mediating role, suggesting that consumer perceptions of corporate social responsibility shape loyalty and purchase intentions. Consumer preference is not only built through product features or price, but also through the emotional connection and social value built by companies through CSR programs. The implication of this study suggests that automotive companies in Pontianak and other regions make CSR a strategic part of brand management and market winning efforts. Consistent, authentic, and communicative CSR implementation can increase positive perceptions of the brand and strengthen the psychological bond between companies and consumers. Thus, CSR becomes an important element in modern sustainable marketing strategies.